Analisis Partisipasi Masyarakat dalam Pembangunan Infrastruktur Jalan pada Program PNPM - Herma Yunita; Dwi Yanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Urban development from the past until now has always been an interesting theme discussed in development discussions, this is because the development of rural / urban villages is an integral as well as a central point of national development. The purpose of this study was to determine community participation in the development of road infrastructure through the PNPM Program in Kelurahan Ponorogo, Lubuklinggau Utara District II. This research is a survey research. The type of data used is primary data obtained from questionnaires, interviews, observations, documentation with the number of respondents 7 neighborhood units (RT) where to be taken are 2 KSM (self-help groups) in 2 RTs in Ponorogo Kelurahan, namely RT 1 and RT 2. The total population of the two Rt is 178 households. The sampling method used was purposive sampling by 50%, so the number of samples to be taken was as many as 89 people. Data analysis methods used are descriptive analysis and qualitative analysis. The results of this study indicate that (1) Participation of the community in the form of mind Ponorogo Village has been going very well, with a percentage of 86.6%. (2) The participation of workers by the community in the construction of road infrastructure is 77.5% with a good category. (3) Community participation in the form of expertise is 55.1% with a fairly good category, (4) Community participation in the form of goods is carried out voluntarily by 100% with a very good category (5) Participation in community money Ponorogo Kelurahan is basically non-existent, however more manifested in the form of consumption, such as providing coffee water, tea water and snacks during mutual assistance in the construction of infrastructure roads through the PNPM Program. Keywords: Community Participation, Road Infrastructure Development, PNPM, Village Ponorogo